Spatial Justice in the Data-Driven City: Towards a Non-representational Paradigm - Tedeschi, Miriam; Verdu Sanmartin, Amalia (Taylor & Francis, 2026)
Given the challenges in theorizing and defining spatial justice in an increasingly data-driven society, this article explores the potential of framing spatial justice and the right to the digital city within non-representational geographies and posthuman theories. It turns to these frameworks as sets of theoretical tools (nonhuman agency, affect, and information moving across physicaldigital, or blended, spaces) unveiling how differences for exclusion are reified in digitalized urban contexts.